(untitled) (Indonesian Minority Justice Review, 2025)
This paper investigates the legal and social barriers to equality for the LGBTQ+ community in Indonesia, particularly in the context of growing conservative religious and political movements. While Indonesian law does not explicitly criminalize homosexuality, the absence of legal protections for LGBTQ+ individuals, coupled with societal discrimination, has created significant challenges in achieving equality. The study examines the legal landscape, including the 1974 Marriage Law, which defines marriage as between a man and a woman, and the 2008 Pornography Law, which has been used to target LGBTQ+ individuals. The paper also explores the social and political environment that influences LGBTQ+ rights, focusing on the increasing hostility from conservative religious groups and the role of local authorities in restricting LGBTQ+ rights through moral policing. Through a combination of legal analysis, interviews with LGBTQ+ activists, and case studies of individuals facing legal persecution, the paper demonstrates how the lack of legal protections coupled with societal stigma perpetuates discrimination and marginalization. The findings suggest that the legal framework in Indonesia remains insufficient to safeguard LGBTQ+ rights, and that broader social and political changes are necessary for achieving full equality. The paper concludes by calling for the introduction of comprehensive anti-discrimination laws and greater advocacy for LGBTQ+ visibility and rights in Indonesian society.